FRI0116 Prevalence of Vertebral Fractures and the Relation to Clinical and Radiological Outcome in Ankylosing Spondylitis Patients with Active Disease. (10th June 2014) - Maas, F.; van der Veer, E.; Brouwer, E.; Bos, R.; Efde, M.; Chaudhry, R.N.; Bootsma, H.; Spoorenberg, A.; Arends, S.
Abstract : Background: Ankylosing spondylitis (AS) is characterized by the combination of inflammation, excessive bone formation, and bone loss in the axial skeleton. This excessive bone loss may lead to the occurrence of vertebral fractures (VF). Objectives: To investigate the prevalence and distribution of VF and their relation to clinical and radiological outcome in AS patients with active disease. Methods: All consecutive patients from the Groningen Leeuwarden AS (GLAS) cohort who visited the outpatient clinic between November 2004 and June 2011 with active disease (Bath AS Disease Activity Index (BASDAI) ≥4 and/or expert opinion) and available spinal radiographs were included. Patients fulfilled the modified New York criteria for AS. Radiographs of the thoracic and lumbar spine were scored using the method of Genant et al., a semiquantitative technique evaluating anterior, middle, and posterior heights of vertebrae Th4 to L4. VF were defined based on reduction in vertebral height: grade 1 (mild): 20-25% reduction; grade 2 (moderate): 25-40% reduction; and grade 3 (severe): >40% reduction. Radiographs of the cervical and lumbar spine were scored for spinal radiographic damage using the modified Stoke AS Score (mSASSS). All radiographs were scored by two independent readers blinded for patient characteristics. Results: 205 AS patients were included; 67% were male, mean age was 42±11 years, median symptom duration was 15 years (range 1-53), 80% were HLA-B27 positive, mean BASDAI was 6.1±1.6, mean ASDAS was 3.8±0.8, and median mSASSS was 11.2 (range 0-72). In total, 2518 vertebrae could be scored and 110 VF (4.4%) were found. Of these VF, 74 were scored grade 1, 34 grade 2, and 2 grade 3. 84% of VF occurred in the thoracic spine (Figure 1 ). The average number of VF per patient was 1.8. Sixty of 205 patients (29%) showed at least 1 VF, of which 33 patients had 1 VF, 16 patients 2 VF, and 11 patients more than 2 VF. Patients with VF were older (mean age 46 vs. 41 years, p<0.01), were more frequently male (77% vs. 63%, p=0.066), had larger occiput to wall distance (median 5.0 vs. 3.5 cm, p<0.05), and had significantly more spinal radiographic damage (median mSASSS 15.6 vs. 9.9, p<0.05) compared to patients without VF. Conclusions: In our cross-sectional observational cohort, the prevalence of VF is 29% in AS patients with active disease. Most VF are located in the middle and low thoracic spine. The presence of VF is associated with older age, male gender, increased thoracic kyphosis, and more spinal radiographic damage. Further longitudinal research is needed to investigate the influence of treatment (e.g. NSAID's, TNF-α blockers) on the development of new VF in AS. Acknowledgements: The GLAS cohort was supported by an unrestricted grant from Pfizer. Pfizer had no role in the design, conduct, interpretation, or publication of this study. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4298